2012
DOI: 10.1055/s-0032-1313337
|View full text |Cite
|
Sign up to set email alerts
|

Primary Reconstruction of Fingernail Injuries in Children with Split-Thickness Nail Bed Grafts

Abstract: Primary reconstruction of complex nail bed injuries with STNBGs usually gives good cosmetic and functional results in children and prevents secondary nail growth disturbances reliably.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…4,13,14 Clayburgh et al and Rohard et al introduced scoring systems which included the surgeon's assessment and patient's satisfaction level. 1,7 Even these objective assessments did not include the function of the fingers like motion and pinch strength. All of them assessed the cosmetic aspect of the nail, for example, irregularity, adherence and splitting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4,13,14 Clayburgh et al and Rohard et al introduced scoring systems which included the surgeon's assessment and patient's satisfaction level. 1,7 Even these objective assessments did not include the function of the fingers like motion and pinch strength. All of them assessed the cosmetic aspect of the nail, for example, irregularity, adherence and splitting.…”
Section: Discussionmentioning
confidence: 99%
“…Sabapathy et al and Rohard et al reported hook nail deformities in cases of inadequate length of distal phalanges. 5,7…”
Section: Case Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Di Napoli et al [18] reports that 6% of 354 torture survivors reported nail removal. Several papers describe nail deformations caused by traumatic nail injuries [19][20][21] and only 2 out of 6 cases that received treatment completely recovered [20].…”
Section: Discussionmentioning
confidence: 99%